Pengaruh Loyalitas Karyawan dalam Meningkatkan Kepuasan Iterhadap IManajemen IKinerja di Tempat Kerja (Perusahaan) - Elya Ramadhani Tambunan; Sekar Sari; Yusnita Ulfah Munthe; Zainarti Zainarti (STIT Sirojul Falah Bogor, 2023)
Companies often struggle to cultivate employee loyalty. It is difficult to get employees who want to stay long in the company. To encourage this, businesses need to create a comfortable work environment where employees can do their best and are less stressed. This will also help them stay with the company and make employees more loyal. Incentives can also be used by the business world to encourage employees to work hard, be responsible and succeed in achieving company goals. This study aims to ensure that business requires employee loyalty so that employees can work independently and collaboratively for the benefit of the company and its members. Working together towards a common goal and being willing to put a lot of effort into achieving it are two ways to build team loyalty. The research data was collected through the use of qualitative methods, field surveys, and employee performance observations. Keywords: loyalty, performance.